Evolution of an ultracold gas in a non-Abelian gauge field: finite temperature effect - Hasan, Mehedi (2023)
The cooling mechanisms of a Fermionic strontium-87 gas are refined in order to study its evolution under a non-Abelian gauge field. Significant attention is paid to the effect of the finite temperature of the gas on the process in question. The efficiency of the loading of atoms in a cross-dipole trap is described in detail, the quantitative performance of the evaporative cooling is calculated, and a degenerate Fermi gas is characterised using a Thomas - Fermi distribution.